Increasing Purchasing Decisions for UMKM Tempe Chips in Banyumas District through User Interface, Social Media Marketing, Price, and Nutrition Labeling with Purchase Intention as a Mediating Variable - Hawa, Sarah Dien; Resa Frafela Rosmi; Angga Ari Prasetyo (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the economic drivers of society. More than 50% of Indonesian people rely on the wheels of economic rotation by becoming MSME actors This study aims to examine the influence between user interface; social media; price and nutrition labeling; purchase intention toward purchase decision. By using quantitative research methods, 97 tempeh chips MSME as a respondent 97 respondents were tested. Data analysis using PLS the result of the reseac   h are user interface, social media, price and nutrition labeling have  a positive effect on prchase intention and purchasing decision. This reseach also shows that purchasing decision becomes intervening variabel between user interface, social media, price and nutrition labeling have  a positive effect on prchase decision.